The Correlation between Stress Level and Degree of Dysmenorrhea on Female Students at SMA Negeri 1 Surakarta - Rahma, Mega Aini; Dewi, Yulia Lanti Ratna; Hidayati, Rosalia Sri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds : Dysmenorrhea is a disorder or menstrual pain in the lower abdomen, buttocks, and spasmodic pain on the medial side of the thigh that may interfere their daily work. One of the risk factors that lead to the occurrence of dysmenorrhea is stress. This study aims to determine the correlation between stress level and degree of dysmenorrhea on female students at SMA Negeri 1 Surakarta. Methods: This study is an observational study with cross sectional approach. This study was conducted in SMA Negeri 1 Surakarta. The sample used was a student who had experienced menstruation, dysmenorrhea and stress, not smoking, not drinking alcohol, not having diseases associated with female reproductive organs, L-MMPI scores with the answer